Building Cross-Border E-Commerce Talent Development Models for Local Applied Universities in the Digital Economy Context - Qi, Jing (Journal of Educational Research and Policies, 2025)
Driven by the “Internet Plus” strategy and the explosive growth of cross-border e-commerce, this study addresses structural contradictions in talent cultivation at local applied universities. The research constructs a dynamic competency development model through industry-education integration and multi-party collaboration, employing a four-dimensional analytical framework of “curriculum dimension, teaching dimension, evaluation dimension, and synergy dimension”. Innovations include modular project-based curricula integrating real enterprise projects, a three-party evaluation mechanism combining teachers’ data, platforms’ data and enterprises’ data, and a tiered base construction plan with cross-regional replication potential. Theoretical contributions advance the “Internet + Education” system through regional empirical evidence, while practical implications provide an actionable paradigm for transforming applied talent cultivation systems in the digital economy era. This research offers empirical evidence and strategies for promoting high-quality regional digital economy development through optimized talent cultivation.